Unravelling drought and salinity stress responses in barley genotypes: physiological, biochemical, and molecular insights - Alsamadany, Hameed; Abdulbaki, Abdulbaki Shehu; Alzahrani, Yahya (Frontiers in Plant Science, 2024)
In the face of escalating environmental challenges, understanding crop responses to abiotic stress is pivotal for sustainable agriculture. The present study meticulously investigates the intricate interplay between drought and salinity stress in barley (Hordeum vulgare L.). Employing three distinct barley genotypes-Traveller, Prunella, and Zahna-we scrutinize their physiological, biochemical, and molecular adaptations under stress conditions. Our findings underscore genotype-specific responses, unravelling the multifaceted mechanisms that govern stress tolerance. Chlorophyll content, a vital indicator of photosynthetic efficiency, exhibits significant variations across genotypes. Salinity stress induces a decline in chlorophyll levels, while drought stress triggers a more nuanced response. Stomatal conductance, a key regulator of water loss, also diverges among the genotypes. Traveller displays remarkable stomatal closure under drought, conserving water, whereas Prunella and Zahna exhibit contrasting patterns. Antioxidant enzyme activities, crucial for combating oxidative stress, fluctuate significantly. Activities of superoxide dismutase (SOD) and catalase (CAT) surge under salinity stress, while drought predominantly impacts SOD. Gene expression profiling reveals genotype-specific signatures, with stress-responsive genes modulating adaptive pathways. Correlation analyses revealed the intricate interplay of the physiological and biochemical parameters. Genotype-specific adaptations, coupled with dynamic physiological and molecular responses, underscore the plasticity of barley's stress tolerance mechanisms. Throughout the study, the Zahna genotype demonstrated notable tolerance in terms of performance. These insights hold promise for breeding resilient cultivars, bolstering food security in an increasingly unpredictable climate. By deciphering the barley stress symphony, we contribute to the harmonious orchestration of sustainable agricultural practices.